Evaluation of Efficacy of Long-term Yogic Training on Vascular Endothelial Function and Cardiovascular Responses in Healthy Individuals (International Journal of Physiology, 2020)
There are numerous studies confirming the positive effects of physical exercise in improving the functionalstatus of vascular endothelium and cardiovascular parameters. However, there is very less scientific dataavailable showing the efficacy of yoga training on vascular endothelium functions and various cardiovascularparameters with large sample size. Hence the study was intended to measure the change in plasma nitricoxide level (NOx), resting heart rate (HR) and resting systolic (SBP) and diastolic blood pressure (DBP).Yoga intervention was given on age matched 200 healthy individuals of both the gender. NOx, Resting HR,SBP and DBP were measured at Baseline and after six months. Data collected was analyzed statisticallyshowed significant elevation in NOx, reduction in HR, SBP and DBP. Positive findings are the suggestive ofimproved vascular endothelial health and cardiovascular responses.